TINJAUAN YURIDIS TERHADAP PENJATUHAN SANKSI PIDANA BAGI PELANGGAR PEMBATASAN SOSIAL BERSKALA BESAR DI MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Aslamiah, Futri; Rahmadan, Davit; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The State of Indonesia is a state based on law (rechtsstaat) not based on power (machtsstaat). Indonesia is a state based on Pancasila and the 1945 Constitution. It is expressly stated in "Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia", which stipulates that “Indonesia is a state of law. Law enforcement efforts carried out by the apparatus are preventive, persuasive, repressive, and cooperative in order to create order and peace in social life. The purpose of this research is to find out the application of the imposition of criminal sanctions on perpetrators of PSBB violators during the Corona Virus Disease (COVID-19) pandemic in the perspective of Indonesian Criminal Law and to determine the application of criminal sanctions to PSBB violators based on the principle of justice. This research is structured using a normative juridical research type, namely finding the truth of coherence, which is carried out by examining secondary legal materials.Data collection techniques used are literature studies and legislation, books, literature, expert opinions, judges' decisions related to the problem and object of research.This research focuses on the study of the provision and imposition of criminal sanctions on violators of large-scale social restrictions (PSBB).From the results of research conducted by the author, there are two main things that can be concluded, firstly, the application of criminal sanctions against perpetrators of PSBB violators during the Corona Virus Disease (COVID-19) pandemic in the perspective of Indonesian Criminal Law is deemed inappropriate because Indonesia adheres to the ultimum remedium principle, meaning that if a If the case can first be resolved by another route, it is better to use that route first. As well as in terms of the formulation of the type of sanctions in the legislation that is not appropriate can be a factor in the emergence and development of crime. Second, regarding the application of criminal sanctions to PSBB violators in the principle of justice, the law should be fair, indiscriminate and subjective, and regulations or regulations must be fair to all levels of society. Judges must think critically because judges in relation to law enforcement are two things that are interrelated and cannot be separated, namely "law and justice" Keywords: Criminal Sanctions- PSBB- Criminal Law